SUBA-Itraconazole for Primary Antifungal Prophylaxis After Allogeneic Hematopoietic Cell Transplantation. (23rd November 2021) - Lindsay, Julian; Othman, Jad; Kong, Yvonne; Yip, Annie; Van Hal, Sebastiaan; Larsen, Stephen; Bryant, Christian; Gibson, John; Kerridge, Ian; Fay, Keith; Stevenson, William; Arthur, Chris; et al.
Abstract: Background: Itraconazole (ITZ) is an effective agent when used as primary invasive fungal disease (IFD) prophylaxis, but is limited by drug tolerability and variability in serum concentrations. A new formulation, SUBA-itraconazole (for "super bioavailability"; S-ITZ), addresses the limitations of conventional ITZ formulations. Methods: We conducted a retrospective cohort study at 2 Australian centers to evaluate the safety, tolerability, and effectiveness of S-ITZ as primary antifungal prophylaxis in hematopoietic cell transplant (HCT) recipients without grade II–IV acute graft-vs-host disease, from day 1 until approximately day 100 (cohort A) or day 1 until neutrophil engraftment (cohort B). A total of 204 patients and 1410 trough plasma ITZ concentrations were assessed. Results: The incidence of breakthrough proven/probable IFD at day 180 was 1.0% (95% confidence interval [CI], .2%–3.2%), with 1.6% in cohort A and 0% in cohort B, and overall fungal-free survival of proven/probable IFD was 82.9% (95% CI, 76.8%–87.4%). Preengraftment early permanent S-ITZ discontinuation was 3.4% overall, with no significant difference between cohorts. No patients required cessation due to gastrointestinal intolerance attributed to S-ITZ. The geometric mean trough plasma ITZ concentration was 1130ng/mL (interquartile range, 566–1801ng/mL; coefficient of variation, 56.57%) and the median time to achieve therapeutic levels was 10 days. Conclusions: S-ITZ is a safe and well-tolerated oral formulation and is a novel alternative for primary IFD prophylaxis after HCT. Abstract : New formulation SUBA-itraconazole (S-ITZ) addresses the conventional formulations limitations of intolerability and variability in absorption. The incidence of breakthrough proven/probable invasive fungal disease at day 180 was 1.0%; no patients required cessation due to gastrointestinal intolerance attributed to S-ITZ.